2019
DOI: 10.1002/jlb.5hi0119-018r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Endotoxin-induced immunotolerance is associated with loss of monocyte metabolic plasticity and reduction of oxidative burst

Abstract: Secondary infections are a major complication of sepsis and associated with a compromised immune state, called sepsis-induced immunoparalysis. Molecular mechanisms causing immunoparalysis remain unclear; however, changes in cellular metabolism of leukocytes have been linked to immunoparalysis. We investigated the relation of metabolic changes to antimicrobial monocyte functions in endotoxin-induced immunotolerance, as a model for sepsis-induced immunoparalysis. In this study, immunotolerance was induced in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 57 publications
2
46
2
Order By: Relevance
“…A recent study using a human in vivo model of endotoxemia, however, showed that ET monocytes cannot induce an oxidative response to Escherichia coli or Candida albicans challenge. This effect was due to a failure of ET monocytes to modify their metabolism during ex vivo LPS restimulation, resulting in reduced Candida killing capacity ( 54 ). However, as most of these studies used different protocols to induce ET, both in vivo and ex vivo , the unambiguous interpretation of the process remains challenging.…”
Section: Sepsis-associated Changes To Phagocyte Subsetsmentioning
confidence: 99%
“…A recent study using a human in vivo model of endotoxemia, however, showed that ET monocytes cannot induce an oxidative response to Escherichia coli or Candida albicans challenge. This effect was due to a failure of ET monocytes to modify their metabolism during ex vivo LPS restimulation, resulting in reduced Candida killing capacity ( 54 ). However, as most of these studies used different protocols to induce ET, both in vivo and ex vivo , the unambiguous interpretation of the process remains challenging.…”
Section: Sepsis-associated Changes To Phagocyte Subsetsmentioning
confidence: 99%
“…For example, the exact exposure time and the amount of pathogens within the blood during sepsis cannot be determined with certainty. Therefore, as another alternative, injection of immune-stimulants, including lipopolysaccharide (LPS), has been performed and investigated in healthy human volunteers ( 8 10 ). On the one hand, this approach provides the intriguing opportunity to study the immunological response directly in human organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining metabolic plasticity is necessary for immune cells to generate anti-pathogen responses when challenged and this appears to be compromised in immunoparalysed cells. For example, monocytes from healthy adults injected with endotoxin have a less pronounced metabolic response to re-stimulation with endotoxin and an associated reduction in pathogen killing in vitro 7 hours post-injection relative to monocytes isolated from donors without pre-exposure to endotoxin (31). Trained immunity may be one mechanism by which innate immune cells adapt to the simultaneous derangement of microbial and nutrient exposures during undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Trained immunity may be one mechanism by which innate immune cells adapt to the simultaneous derangement of microbial and nutrient exposures during undernutrition. Children with SAM share many of the clinical features of sepsis, which is a common clinical complication of SAM and a recognized stimulus for monocyte training (3133). During sepsis, epigenetic modifications in monocytes down-regulate pro-inflammatory cytokine production but upregulate alternative functional genes, including antimicrobial peptides (AMP) (32, 33).…”
Section: Introductionmentioning
confidence: 99%